Metode Tafsir Tahlili: Cara Menjelaskan al-Qur’an dari Berbagai Segi Berdasarkan Susunan Ayat-ayatnya - Amin, Faizal (KALAM, 2017)
This article examines a method of tafsīr taḥlīlī or quranic analytical method as one of the four prominent interpretation procedures to explain the content of Quran.  The existence of quranic interpretation is an intrinsically-extrinsically necessity for the primer resources of Islamic teaching.  The method of tafsīr taḥlīlī is an interpretation procedure to explain the content of Quran from many different aspects based on quranic sequences of verses.  The method of tafsīr taḥlīlī gives the freedom and the wide space of interpretation for Mufassir to make quranic explanation from the first verse untill the last one.  It is provided systematically and comprehensively based on the Mufassir’s competences and efforts. Nevertheless, every method has its own advantages or superiorities in some aspects on the one hand, as well as has its own weakness on the other hand.  The superiorities and weakness of the quranic interpretation methods do not mean a negative account, but those role as early warning systems for Mufassir to be more careful whenever interprate any verses of Quran.  There for, they can avoid some mistakes in producing the quranic interpretation.